Determinant factors affecting environmental, social and governance (ESG) disclosure - Valentino Ardian Perdana; Muslich Anshori (Keberlanjutan)
This study aims to determine factors affecting Environment, Social, and Governance (ESG) disclosure. This study uses secondary data from the CSRHub index and data from annual reports of companies listed on the Indonesia Stock Exchange (IDX). The research period is twelve years (2009-2020). This study uses linear regression analysis. The study indicates that the director's size, environment and social committee, domestic ownership, and concentration ownership have a significant positive effect. Domestic factors such as environment and social committee, domestic ownership, and concentration ownership affect ESG disclosure.